الأعجاز الغيبي في القران الكريم ودراسة تطبيقية - نصيف، شهلاء صبيح (الجامعة المستنصرية - كلية التربية الأساسية, 2015)
بعد الاستعانة والتوكل على الله وبعد أتمام البحث الموسوم (بالإعجاز الغيبي في القرآن الكريم) - دراسة تطبيقية- تناولت الباحثة في الفصل الأول معنى الإعجاز في اللغة والاصطلاح ومعنى الغيب في اللغة والاصطلاح وتناولت أهم وأشهر العلماء الذين بحثوا في الإعجاز الغيبي منهم الرماني والخطابي والباقلاني وغيرهم وقد تعرضت الباحثة في الفصل الثاني إلى أنواع الإعجاز الغيبي فكان على نوعين: الأول: ما يتعلق بالأشياء المادية والثاني: يتعلق بالأشياء غير المادية، وتناولت أيضا الألوان الإعجاز الثلاث هي 1. غيب الماضي 2. غيب الحاضر 3. غيب المستقبل وكانت الغيبيات الخمسة التي ذكرها الله تعالى في كتابه العزيز هي 1. علم الساعة 2. إنزال الغيث 3. هو الذي يعلم ما في الأرحام 4. ما تدري نفس ماذا تكسب غدا 5. وما تدري نفس بأي ارض تموت، وقد توصلت الباحثة إلى أن كلمة الإعجاز تعود إلى السبق والفوت عن الشيء في المعنى اللغوي، وكلمة الغيب تعود إلى معنى واحد هو الاستتار أذن فالغيب في القرآن الكريم ينقسم إلى أقسام كثيرة كما ذكرناه أنفا حيث ذكرها الله تعالى في القرآن في سورة لقمان ولم يطلع عليها أحدا من خلقه بل اختصها لنفسه عز وجل.
After use and strive to God Almighty and after completion of the research subject b (unseen miracles in Quran). case study – dealt with in chapter I on the deficits in language, terminology and meaning unseen in language, terminology and dealt with the most important and famous scientists who discussed in miracle unseen of them: Roman, rhetorical and albaklani and other scientists reported in chapter II types of metaphysical miracles were of two types : Type 1:-on material things, and the second type:-the non-physical objects. the faces of miracle plays a prominent role in this research the three colors are:-1-last 2-Gibb Gibb present 3-Gibb future. And five of the occult by Allaah in the Qur'aan are:-1-2-hour science take down Al 3-who knows what is in the wombs what training the same what you earn on what training the same as any land die. The researcher concluded that the word miracles returns to previously and the passing of the thing in the linguistic sense, and the unseen back to meaning one is legalistic, and unseen in the Qur'an is divided into many sections, including the unseen in the past, the present and the future, according to the
Keywords: الاعجاز الغيبي -- إعجاز القرآن -- القرآن الكريم